2016
DOI: 10.18632/oncotarget.12371
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression and potential roles of NRIP1 in psoriasis

Abstract: Nuclear receptor interacting protein 1 (NRIP1, also known as RIP140) is a co-regulator for various transcriptional factors and nuclear receptors, and has been shown to take part in many biological and pathological processes, such as regulating mammary gland development and inflammatory response.The aim of this study is to investigate the expression of NRIP1 and to explore its roles in the pathogenesis of psoriasis. Thirty active psoriasis patients and 16 healthy volunteers were enrolled for this study. qRT-PCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 20 publications
2
18
0
Order By: Relevance
“…Psoriasis and these comorbidities share a number of same inflammatory cytokines, such as Th1 and Th17 inflammatory molecules, which promote a proinflammatory state . The combination of our previous studies in metabolism and psoriasis have resulted in the identification of a psoriasis gene, NRIP1 (Luan et al, 2016). This study showed another candidate gene, PCSK9, which plays an important role in metabolism and has the potential to be a therapeutic target for treatment of psoriasis.…”
Section: Association Between Metabolic Disorders and Psoriasis Providmentioning
confidence: 91%
“…Psoriasis and these comorbidities share a number of same inflammatory cytokines, such as Th1 and Th17 inflammatory molecules, which promote a proinflammatory state . The combination of our previous studies in metabolism and psoriasis have resulted in the identification of a psoriasis gene, NRIP1 (Luan et al, 2016). This study showed another candidate gene, PCSK9, which plays an important role in metabolism and has the potential to be a therapeutic target for treatment of psoriasis.…”
Section: Association Between Metabolic Disorders and Psoriasis Providmentioning
confidence: 91%
“…In psoriasis, numerous effector cells including keratinocytes, Th17 cells, and dendritic cells activated by TNF-α, plasmin and TLRs could produce cytokines and chemokines via the NFκB pathway, which leads to psoriatic phenotypes (140). Moreover, our recent studies reported that metabolic-associated genes PCSK9 and nuclear receptor interacting protein 1 (NRIP1) both play important roles in psoriasis via the NFκB pathway (115, 141). It has been reported that PCSK9 silencing can suppress atherosclerosis by inhibiting the TLR4/NFκB signaling pathway (142).…”
Section: Mechanisms Of Mets and Skin Diseasesmentioning
confidence: 99%
“…NFκB (RelA) can inversely resolute the inflammatory response by targeting and degrading NRIP1 via recruiting the SCF (Skp, culin, F-box-containing) E3 ligase complex (145). Our laboratory revealed that suppression of NRIP1 in CD4+ T cells that were isolated from psoriasis patients could downregulate the expression of RelA/p65 and decrease the secretion of IL-17, thus inhibiting the inflammation in psoriasis (141). Importantly, together, PCSK9 and NRIP1 may be two potential therapeutic targets for both psoriasis and metabolic syndrome by regulating the NFκB-associated chronic inflammatory status.…”
Section: Mechanisms Of Mets and Skin Diseasesmentioning
confidence: 99%
“…Moreover, animal studies showed that imiquimod-induced inflammation was delayed in knockout NRIP1 mice. The authors suggested that NRIP1 could induce abnormal proliferation and apoptosis of keratinocytes through direct interaction with Re1A/p65 [106].…”
Section: Additional Inflammatory Pathways In Psoriasismentioning
confidence: 99%